Penerapan Hukum Militer Terhadap Anggota Militer Yang Melakukan Desersi Berdasarkan Kitab Undang- Undang Hukum Pidana Militer - Akhmad Alfin; Esti Ningrum; Agoes Djatmiko; Haris Kusumawardana (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
The aim of this research is to determine the process of applying military law to military members who commit the crime of desertion based on the military criminal code and to find out the obstacles to military law against military members who commit the crime of desertion based on the military criminal code. The type of research in writing this thesis is normative juridical research, and the approach method used is law, analytical and case approaches with clinical legal research writing of a perspective nature. The data collection technique was a literature study. The results show that the application of military criminal law to members of the Indonesian National Army who are proven to have committed a criminal act of desertion is the authority of the military court to try them, then the stages are in the form of investigations carried out by the Military Police on the orders of a superior who has the right to punish (Ankum). Then the investigation file is given to the military prosecutor to be studied, then the military prosecutor makes the indictment to be submitted to the military court, after the court feels that the files from the military prosecutor are sufficient, the military court will try military personnel accused of desertion. Furthermore, the constraints in law enforcement related to the crime of desertion are viewed from 4 interrelated aspects, namely concerning the substance of the law, the legal structure itself, facilities or infrastructure, and society. Settlement of cases in military justice is currently well regulated, however, it is hoped that all those who play a role in the military case settlement process carry out all these stages based on Justice and Positive Law. Keywords: Desertion, Indonesia Military, Military Crime